Risk factors for diabetic nephropathy among newly diagnosed type 2 diabetic patients with normal blood pressure (BIRDEM Medical Journal, 2022)
Background: Patients with type 2 diabetes mellitus (T2DM) pass through pre-diabetic stages and during diagnosis, half of them may have different complications including diabetic nephropathy. Hypertension has adverse impacts on diabetic nephropathy. We aimed to evaluate the risk factors for diabetic nephropathy among newly detected T2DM patients with normal blood pressure.Methods: A case-control study was done at a tertiary care hospital in Dhaka, Bangladesh from January 2018 to June 2019. Newly detected (